Sediaan Antiketombe Emulsi Encer Ekstrak Bunga Kenanga (Cananga odorata): Pengaruh Peningkatan Konsentrasi Ekstrak Terhadap Sifat Fisikokimia dan Efektivitasnya Terhadap Malassezia furfur - Ramadhan, Rizki Aulia; Nurwaini , Setyo (Journal of Pharmaceutical and Sciences, 2026)
Background: Dandruff is a common scalp disorder affecting approximately 50% of the global population. Dandruff treatment generally relies on chemical-based shampoos, which may cause adverse effects with long-term use. Therefore, natural-based alternatives are needed. Ylang-ylang flower (Cananga odorata) extract contains flavonoids and saponins with potential antifungal activity. To develop an effective, stable, safe, and user-friendly natural anti-dandruff product, evaluation of its physicochemical properties and antifungal efficacy is required. Objective: This study aimed to investigate the effect of increasing concentrations of ylang-ylang flower extract on the physicochemical properties of an anti-dandruff dilute emulsion and its inhibitory activity against Malassezia furfur. Methods: ylang-ylang flowers were extracted by maceration using ethanol as a solvent at a 1:5 ratio. The extract was formulated into four formulations with concentrations of F1 (10%), F2 (15%), F3 (20%), and F4 (25%), along with a formulation without extract (F0) as a control. Physicochemical evaluations included organoleptic properties, homogeneity, and pH value, while antifungal activity was assessed using the microdilution method. The pH value data were analyzed using one-way ANOVA while the freeze-thaw data were analyzed using two-way ANOVA. Results: Statistical analysis showed that the addition of ylang-ylang flower extract significantly improved the pH stability of the formulation compared to the control (F0) (p < 0.05). The irritation test indicated that all formulations did not cause irritation in volunteers. The microdilution assay revealed that the MIC of the extract was 390.625 µg/mL, while the MIC values of the formulations containing the extract at different concentrations were 312.5 µg/mL (F1), 468.75 µg/mL (F2), 312.5 µg/mL (F3), and 390.625 µg/mL (F4). These values were higher than that of ketoconazole, which exhibited an MIC of 0.058 µg/mL. Conclusion: Increasing concentrations of ylang-ylang flower extract significantly affected the physicochemical properties of the formulation by improving pH stability and demonstrated good antifungal activity against Malassezia furfur.